DEVELOPMENT OF AN AUTOMATED PHOTOVOLTAIC SYSTEM WITH WIRELESS MONITORING - Kuttybay, N.B.; Saymbetov, A.K.; Tenizbayeva, Z.Sh.; Smail, L.B.; Yerbolat, R.M. (Academic Scientific Journal of Computer Science, 2021)
The work is devoted to the development of an efficient photovoltaic installation with automated wireless monitoring based on the LabView software. Long-distance communication technology - LoRa was used to wirelessly transmit data on the output characteristic states of the photovoltaic installation, storage battery and built-in sensors. This module operates at 433 MHz and transmits small data packets with low power consumption. This makes the stand-alone system energy efficient compared to similar wireless installations. The graphical software LabView was chosen to monitor the state of the developed system. The paper shows a block diagram of an automated wireless system, an operational algorithm of the external transmitting part of the installation, as well as electrical circuits of the transmitting and receiving control units. As a result of the work, a photovoltaic system with an automated wireless monitoring system and graphical data display was developed. The developed automated complex is more efficient and easy to use in comparison with other systems.